Conservation cost‐effectiveness: a review of the evidence base. Issue 5 (6th January 2021) - Pienkowski, Thomas; Cook, Carly; Verma, Megha; Carrasco, Luis Roman
Abstract: Prioritizing conservation interventions based on their cost‐effectiveness may enhance global conservation impact. To do this prioritization, conservation decision‐makers need evidence of what works where and how much it costs. Yet, the size, representativeness, and strength of the cost‐effectiveness evidence base are unknown. We reviewed conservation cost‐effectiveness studies, exploring the representation of different types of conservation interventions, habitats and locations, and the methods used. Studies were included if they were published in conservation science or related fields before 2017; were peer‐reviewed; reported costs and conservation‐effectiveness or ratios; and were based on empirical data. From an initial search of 13, 184 articles, 91 were considered eligible. We found that the number of cost‐effectiveness studies were growing but remain small. Many common conservation interventions were poorly represented, and there were large geographical biases, with few studies in the world's more biodiverse regions. This sparse and patchy evidence may result from challenges faced when conducting cost‐effectiveness analysis. However, some of these challenges are not unique to cost‐effectiveness studies, and others could be overcome through the use of standardized reporting methods. The reward for overcoming these challenges, and strengthening the evidence base, could be a significant and much‐needed improvement in global conservation.